MOTOR COORDINATION DISORDER IN MAINSTREAM PRIMARY SCHOOL CHILDREN (Fiep Bulletin - online, 2014)
Effective interaction of a child with her/his environment involves a wide range of motor tasks. These vary from relatively simple movement tasks performed in relatively stable situations, such as building blocks and drawing to rather complex actions performed under unpredictable contexts, such as ball games. Lack of movement competence affects the degree to which a child can function independently and effectively within her/his environment. The term Developmental Co-ordination Disorder (DCD) was adopted by the American Psychiatric Association to describe the condition in which a marked impairment in the motor co-ordination of primary school children's is neither explicable by mental retardation nor by any known physical disorder. DCD has been found to have long-term social, emotional, and academic impact, to affect children's attitude towards physical activities and to be a risk factor for obesity in childhood and early adolescence. In this paper we intend to draw the reader's attention mainly to the characteristics of the DCD, its impact on the child's development and identification issues. This is because it is believed that professionals from physical education, sports sciences and related areas must be aware of findings on this subject as they can make significant contribution for the discussion about scientific knowledge on DCD.